Implementation of a pilot telehealth programme in community palliative care: A qualitative study of clinicians' perspectives. (April 2016) - Collier, Aileen; Morgan, Deidre D; Swetenham, Kate; To, Timothy HM; Currow, David C; Tieman, Jennifer J
Background: Telehealth technologies are an emerging resource opening up the possibility of greater support if they have utility for patients, carers and clinicians. They may also help to meet health systems' imperatives for improved service delivery within current budgets. Clinicians' experiences and attitudes play a key role in the implementation of any innovation in service delivery. Aim: To explore clinicians' perspectives on and experiences of the utilisation of a pilot telehealth model and its integration into a specialist community palliative care programme. Design: Focus groups and interviews generated data that were analysed through the lens of a realistic evaluation theoretical framework. Setting/participants: The study was conducted in a metropolitan specialist palliative care service in South Australia. Participants (n = 10) were clinicians involved in the delivery of community specialist palliative care and the piloting of a telehealth programme. Results: Service providers consider telehealth resources as a means to augment current service provision in a complementary way rather than as a replacement for face-to-face assessments. Introducing this technology, however, challenged the team to critically explore aspects of current service provision. The introduction of technologies also has the potential to alter the dynamic of relationships between patients and families and community palliative care clinicians. Conclusion: Implementation of a pilot telehealth programme in a specialist palliative community team needs to involve clinical staff in service redesign from the outset. Reliable IT infrastructure and technical support is critical for telehealth models to be effective and will aid uptake.